2018
DOI: 10.1093/cid/ciy265
|View full text |Cite
|
Sign up to set email alerts
|

Feeding-Related Gut Microbial Composition Associates With Peripheral T-Cell Activation and Mucosal Gene Expression in African Infants

Abstract: These data suggest that nonexclusive breastfeeding alters the gut microbiota, increasing T-cell activation and, potentially, mucosal recruitment of HIV target cells. Study findings highlight a biologically plausible mechanistic explanation for the reduced postnatal HIV transmission observed in EBF infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 44 publications
0
22
1
Order By: Relevance
“…Prior studies have reported increased bacterial species richness or diversity in non-EBF vs. EBF 28 and/or trends of increased bacterial diversity across EBF, non-EBF and non-BF. 29,31,32 However, studies report different indices, analyze data in different ways and some do not account for age of infants at the time of stool sample collection, which is associated with breastfeeding status and infant gut microbiota.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…Prior studies have reported increased bacterial species richness or diversity in non-EBF vs. EBF 28 and/or trends of increased bacterial diversity across EBF, non-EBF and non-BF. 29,31,32 However, studies report different indices, analyze data in different ways and some do not account for age of infants at the time of stool sample collection, which is associated with breastfeeding status and infant gut microbiota.…”
Section: Discussionmentioning
confidence: 97%
“…Processed and partially processed 16S rRNA gene sequence data of stool samples were obtained from seven previously published studies 3,5,18,28,29,31,35 . Of the included studies, three were from the US, one from Canada, one from Haiti, one from South Africa and one from Bangladesh.…”
Section: Data Sources and Study Populationmentioning
confidence: 99%
See 3 more Smart Citations